2010
DOI: 10.1021/la1033959
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Highly Stable Selenium Nanoparticles Capped with Hyperbranched Polysaccharide in Water

Abstract: Water-dispersible selenium nanoparticles (SeNPs) were created by using natural hyperbranched polysaccharide (HBP) as the stabilizer and capping agent under extremely safe conditions. The structure, morphology, size, and stability of the nanocomposites were investigated by transmission electron microscopy (TEM), atomic force microscopy (AFM), and static and dynamic light scattering (DLS) measurements. The results revealed that the spherical selenium nanoparticles (mean particle size of about 24 nm) were ligated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 48 publications
0
65
0
Order By: Relevance
“…But there are reports of preparation of Se nanoparticles with hyperbranched polysaccharide in water [39]. However, it was not prepared for any biological applications.…”
Section: Resultsmentioning
confidence: 99%
“…But there are reports of preparation of Se nanoparticles with hyperbranched polysaccharide in water [39]. However, it was not prepared for any biological applications.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reviews of the role of Se in IBD have concluded that Se status and adequate dietary Se supply are of pivotal importance to colonic inflammation [26, 28]. Nanoparticles that include elemental Se (SeNPs) as a novel form of this nutrient appear to be more effective than that of other Se sources because of their excellent bioavailability, biological activity, and low toxicity [29]. To address application of ULP-SeNPs to prevent IBD, we developed a stable, homogeneous formulation of ULP-SeNPs with consistent diameter of 130 nm.…”
Section: Discussionmentioning
confidence: 99%
“…20,[44][45][46] Various sizes of selenium nanoparticles can be obtained by changing the concentration of a protein such as bovine serum albumin. 47,48 Generally, the higher the bovine serum albumin concentration, the smaller the selenium nanoparticle size.…”
Section: Discussionmentioning
confidence: 99%